Prediction of vascular dementia and Alzheimer's disease in patients with atrial fibrillation or atrial flutter using CHADS2 score - Chou, Ruey-Hsing; Chiu, Chun-Chih; Huang, Chin-Chou; Chan, Wan-Leong; Huang, Po-Hsun; Chen, Yu-Chun; Chen, Tzeng-Ji; Chung, Chia-Min; Lin, Shing-Jong; Chen, Jaw-Wen; Leu, Hsin-Bang (Journal of the Chinese Medical Association, 2016)
Background - Atrial fibrillation (AF) is associated with an increased risk of dementia. However, limited data are available on the predictors of dementia in patients with AF. This study aimed to evaluate whether the CHADS2 score could be a useful tool for risk stratification with regard to dementia occurrence among patients with AF. - Methods - AF patients were identified from the National Health Insurance sampling database, which has accumulated a total of 1,000,000 participants since 2000. After excluding patients diagnosed with dementia prior to the index day of enrollment, CHADS2 score was measured to investigate its association with the occurrence of dementia, including vascular dementia and Alzheimer's disease. - Results - During the mean follow-up period of 3.71 ± 2.78 years, 1135 dementia cases (7.36%) were identified, including 241 cases of vascular dementia and 894 cases of Alzheimer's disease. In multivariate analysis, an increase of 1 point in the CHADS2 score was independently associated with a 54% increase in the risk of vascular dementia (hazard ratio = 1.54; 95% confidence interval, 1.41-1.69; p < 0.001) and a 40% increase in Alzheimer's disease (hazard ratio = 1.40; 95% confidence interval, 1.34-1.46; p < 0.001). - Conclusion - CHADS2 score is a useful predictor for the development of vascular dementia as well as Alzheimer's disease in patients with AF.
Gesehen am 04.05.2020